Biogenic metallic nanoparticles: biomedical, analytical, food preservation, and applications in other consumable products - Kumar, Ashwini; Shah, Sunny R.; Jayeoye, Titilope J.; Kumar, Akash; Parihar, Akshay; Prajapati, Bhupendra; Singh, Sudarshan; Kapoor, Devesh U. (Frontiers in Nanotechnology, 2023)
Biogenic metallic nanoparticles (BMNPs) are nanostructure materials synthesized through biological processes that have gained significant attention due to their small size and high surface area-to-volume ratio. BMNPs have several advantages over chemically synthesized ones due to their eco-friendly synthesis regimen, sustainability, biocompatibility, and diverse multifarious biomedical applications. Moreover, the superior cytocompatibility and stability due to the capping layer over metallic nanoparticles (MNPs), reduces the like hood of toxicity and side effects, making them a safer alternative to traditional drug delivery methods. Among several promising applications of BMNPs, their antibacterial activity, analytical sensing of heavy metals, and their roles in food preservations have been widely explored. In addition, to drug delivery and imaging, BMNPs have also been investigated for therapeutic activity such as antimicrobial efficacy against the skin and soft tissue nosocomial pathogens and targeting cancer cells in cancer therapy. The present review bestows several characterization techniques involved with MNPs and compressive aspects of the biogenic synthesis of MNPs using agricultural and biological materials, which reduces the cost of synthesis and minimizes the use of hazardous chemicals. The review also focuses on the multifold applications of BMNPs including biomedical, analytical, preservation of food, and in other consumable goods with toxicological aspects.